Effect of Eight Weeks Endurance Training and nNOS Inhibition on Skeletal Muscle Agrin levels in Old Rats - مجتبی صالح پور; مریم نورشاهی; فریبا خداقلی; حمید رجبی (Shahid Beheshti University, 2014)
Purpose: The structure and function of neuromuscular junction (NMJ) changes significantly such as decrease nNOS activity during aging and results in decrease of physical performance and sarcopenia. The purpose of this study was to determine the effect of eight weeks of endurance training and neuronal nitric oxide synthase (nNOS) inhibition on skeletal muscle agrin levels in old rats. Methodology: Endogenous NO production was blocked by two administering NG-nitro-L- arginine methyl ester (LNAME) dosages (25 and 100 mg.kg 1.day1) solved in drinking water. Forty eight old male Wistar rats (20 months) were randomly divided into six groups: Control, LNAME25, LNAME100, endurance training with LNAME25, endurance training with LNAME100 and training. LNAME treatment began three days before exercise protocol and continued until the last day. Endurance training groups were exercised on treadmill for 8 weeks, 5 times a week and 60 minutes a day at velocity up to 28 m/min progressively. Forty eight hours after last session of exercise training, animals were anesthetized and soleus and Extensor digitorum longus (EDL) were removed. Results: Western Blotting analysis revealed that Soleus and EDL muscles agrin content in Training+ LNAME 25,100 and Training groups were significantly higher than control group (P<0.05) and LNAME 100 mg.kg"1.day1 treatment significantly decreased agrin content in these muscles (P<0.05). Conclusion: It seems that decrease in nNOS activity during aging, could be responsible for decrease in agrin level and NMJ weakness. Our data suggested that daily endurance training could increase agrin level even in rats which received LNAME. In general, daily training could be a suitable route to reduce sarcopenia in aged population.